ANALISIS FLYPAPER EFFECT PAD DAN DAU TERHADAP BELANJA DAERAH DI PROVINSI KALIMANTAN TIMUR TAHUN 2010-2014 - Nabilah, Aisyah Najibah; Soelistyo, Aris; Kusuma, Hendra (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2016)
This research purposed to know the effect of PAD and DAU toward regional expenditure in the country /city in East Kalimantan province and to know whether flypaper occur in the country/City of East Kalimantan Province in the 2010-2014.The instrument used in this research was the analysis of data panel regression. The results of this research showed that the local revenue (PAD) and (DAU) was took effect regional expenditure significantly. PAD took effect DAU toward regional expenditure, but DAU did not affect significant toward regional expenditure. During the period of this research did not happen flypaper in country/cityinthe ProvinceofEastKalimantan.ANALISIS FLYPAPER EFFECT PAD DAN DAU TERHADAP BELANJA DAERAH DI PROVINSI KALIMANTAN TIMUR TAHUN 2010-2014